2007
DOI: 10.1093/molehr/gam001
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt And ERK1/2 signalling pathways are involved in endometrial cell migration induced by 17β-estradiol and growth factors

Abstract: Cell motility and invasion are crucial events for endometrial cells, not only for the establishment of pathological states but also during the physiological tissue remodelling that occurs during the menstrual cycle and embryo implantation. We have characterized these phenomena in endometrial stromal cells evaluating cell migration-specific stimuli and the biochemical pathways involved. Ability of endometrial cells to migrate on collagen type IV substrate was evaluated by means of chemotaxis experiments. Modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 23 publications
7
98
0
Order By: Relevance
“…In contrast to these observations, death effector domain-containing protein (Dedd) K/K mice implantation sites exhibited decreased AKT protein levels, accompanied by a structural disintegration of the sites and implantation failures; forced expression of AKT1 partially restored polyploidy of the decidual cells, an important marker of successful decidualization, and thus, receptive endometrium (Mori et al 2011). AKT has also been shown to regulate endometrial cell migration in response to chemoattractants (PDGF-BB, EGF, and FGF2) as well as 17b-estradiol (E 2 ), further cementing AKT role in the dynamic process of decidualization (Gentilini et al 2007). In farm animals, a very recent report has shown that IGF1 provided a crucial stimulatory signal in primary porcine trophectoderm cells (pTr), through the PI3K/Akt pathway.…”
Section: Implantationmentioning
confidence: 99%
“…In contrast to these observations, death effector domain-containing protein (Dedd) K/K mice implantation sites exhibited decreased AKT protein levels, accompanied by a structural disintegration of the sites and implantation failures; forced expression of AKT1 partially restored polyploidy of the decidual cells, an important marker of successful decidualization, and thus, receptive endometrium (Mori et al 2011). AKT has also been shown to regulate endometrial cell migration in response to chemoattractants (PDGF-BB, EGF, and FGF2) as well as 17b-estradiol (E 2 ), further cementing AKT role in the dynamic process of decidualization (Gentilini et al 2007). In farm animals, a very recent report has shown that IGF1 provided a crucial stimulatory signal in primary porcine trophectoderm cells (pTr), through the PI3K/Akt pathway.…”
Section: Implantationmentioning
confidence: 99%
“…The effects of estradiol (E 2 ) on reproductive tract structure and function are well known. Recently, however, studies have indicated a role for E 2 in tumor initiation and progression through its promotion of the proliferative, migratory and invasive capabilities of cells (2)(3)(4)(5)(6). Many of the changes that occur in the endometrium during tumorigenesis are similar to those observed during implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Embryo implantation is a complex physiological process and depends on a series of key events, including blastocyst migration, apposition and adhesion to the luminal epithelium, extensive degradation and remodeling of extracellular matrix, invasion of the maternal endometrium by the trophoblast cells of the developing blastocyst, and secretion of embryonic factors, which elicit a cellular reaction in the maternal endometrium (Carson et al 2000, Achache & Revel 2006, Gentilini et al 2007. Numerous signaling proteins such as ERKs, phosphatidylinositol 3-kinase (PI3K), RHO/ROCK, PTK2, or PI3K/AKT/mammalian target of rapamycin (MTOR) are involved in the process to coordinate and integrate these events so as to guarantee successful implantation (Pollheimer & Knofler 2005, Gentilini et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous signaling proteins such as ERKs, phosphatidylinositol 3-kinase (PI3K), RHO/ROCK, PTK2, or PI3K/AKT/mammalian target of rapamycin (MTOR) are involved in the process to coordinate and integrate these events so as to guarantee successful implantation (Pollheimer & Knofler 2005, Gentilini et al 2007.…”
Section: Introductionmentioning
confidence: 99%